2020
DOI: 10.1016/j.breast.2020.05.004
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of menstruation persistence or recovery after chemotherapy on survival in young patients with hormone receptor negative breast cancer

Abstract: Introduction: Hormone replacement therapy can diminish hormone depletion-related complaints in postmenopausal women, but is contraindicated for postmenopausal breast cancer (BC) patients. Recovery of menstruation after chemotherapy-induced amenorrhea in young hormone receptor-negative BC patients however, is accepted. To determine the safety of this strategy, we investigated the effect of recovery of menstruation on disease-free survival (DFS) and overall survival (OS) in young hormone receptor-negative BC pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In light of this potential misclassification bias, it is of interest that two retrospective studies that considered temporary and permanent amenorrhea as separate exposures, found a trend towards an increased recurrence risk in women with HR-negative BC and a persistent menstrual cycle or recovery after amenorrhea (HR 1.45; 95% CI 0.83–2.54 and HR 1.73, 95% CI 0.86–3.48, respectively) [ 15 , 16 ]. Interestingly, a retrospective study on risk-reducing salpingo-oophorectomy (RRSO, i.e., preventive surgical ovarian and fallopian tube removal) after BC diagnosis in BRCA -mutation carriers found a strong protective effect on recurrence for ER-negative BC patients, but not ER-positive BC patients [ 17 ].…”
Section: Clinical Evidence For a Role Of Estrogen And Progesterone In Tnbcmentioning
confidence: 99%
“…In light of this potential misclassification bias, it is of interest that two retrospective studies that considered temporary and permanent amenorrhea as separate exposures, found a trend towards an increased recurrence risk in women with HR-negative BC and a persistent menstrual cycle or recovery after amenorrhea (HR 1.45; 95% CI 0.83–2.54 and HR 1.73, 95% CI 0.86–3.48, respectively) [ 15 , 16 ]. Interestingly, a retrospective study on risk-reducing salpingo-oophorectomy (RRSO, i.e., preventive surgical ovarian and fallopian tube removal) after BC diagnosis in BRCA -mutation carriers found a strong protective effect on recurrence for ER-negative BC patients, but not ER-positive BC patients [ 17 ].…”
Section: Clinical Evidence For a Role Of Estrogen And Progesterone In Tnbcmentioning
confidence: 99%